Pengukuran Keandalan Alat Keruk Kapal Isap Produksi Timah 7 Menggunakan Pendekatan Overall Equipment Effectiveness (OEE) - Iqbal Fadhilsyah; Indra Feriadi; Erwansyah Erwansyah (Politeknik Negeri Lhokseumawe, 2026)
Production Suction Dredger (KIP) are the primary equipment for offshore tin mining, operating with a hydraulic system to drive the dredge, significantly impacting production efficiency. This study aims to measure and analyze the reliability of the dredge at KIP Timah 7 using a partial approach to the Overall Equipment Effectiveness (OEE) method, focusing on two main components: availability and performance. Data were obtained from operational reports for the 2023–2024 period, covering downtime, uptime, and monthly disruptions. The data will be processed monthly to obtain availability and performance values, then combined to calculate OEE as an indicator of work Effectiveness. The results show that availability fluctuates between 81.30% and 100%, while performance remains constant at 100% because actual operating time meets the ideal target. The OEE value varies following changes in availability each month. The disruption analysis identified the soil pump cardan shaft, soil pump, and press pipe as the most frequently damaged components, increasing downtime. Therefore, scheduled maintenance is required on these critical components to improve work efficiency while minimizing potential production disruptions.